Because they marched : the people's campaign for voting rights that changed America - Freedman, Russell, 1929-2018 (Holiday House, 2014)
To commemorate the 50th anniversary of the 1965 march for voting rights from Selma to Montgomery, Alabama, Newbery Medalist Freedman presents a riveting account of this pivotal event in the history of civil rights.